Overnight heart rate variability and next day cortisol response during simulated on-call conditions. (November 2019) - Vincent, Grace E.; Jay, Sarah M.; Preece, Helen; Hall, Sarah J.; Aisbett, Brad; Baumert, Mathias; Sprajcer, Madeline; Lack, Leon; Ferguson, Sally A.
Highlights: Laboratory-based on-call work had relatively little impact on physiological stress. Knowledge of definitely being woken slightly increased overnight physiological stress. Anticipating a high-stress task slightly increased next-day physiological stress. Further research on physiological stress during real-world on-call work is needed. Abstract: Objective: This study had two specific objectives, 1) to investigate the impact of being on-call on overnight heart rate variability during sleep and; 2) to examine whether being on-call overnight impacted next-day salivary cortisol concentrations. Methods: Data are reported from three within-subject laboratory studies (n = 24 in each study) that assessed varying on-call conditions. Healthy male participants (n = 72 total) completed a four-night laboratory protocol, comprising an adaptation night, a control night, and two counterbalanced on-call nights with varying on-call conditions. These on-call conditions were designed to determine the impact of, Study 1: the likelihood of receiving a call ( definitely, maybe), Study 2: task stress ( high-stress, low-stress), and Study 3: chance of missing the alarm ( high-chance, low-chance), on measures of physiological stress. Overnight heart rate variability (HRV) (during sleep) was measured using two-lead electrocardiography, and time- and frequency-domain variables were analysed. Saliva samples were collected at 15-min time intervals from 0700-0800 h to determine cortisol awakening response outcomes and at four daily time points (0930 h, 1230 h, 1430 h, and 1730 h) to assess diurnal cortisol profiles. Results: There were few differences in HRV measures during sleep across all three studies. The only exception was in Study 1 where the standard deviation of the time interval between consecutive heartbeats and the root mean square of consecutive differences between heartbeats were lower across all sleep stages in the definitely condition, when compared to control . Across all three studies, being on-call overnight also had little impact on next-day cortisol awakening response (CAR), with the exception of Study 2 where the 1) CAR area under the curve with respect to increase was blunted in the high-stress condition, compared to the control and low-stress conditions and, 2) CAR reactivity was higher in low-stress condition, compared with the high-stress condition. In Study 1, diurnal cortisol area under the curve with respect to ground was lower in the on-call conditions ( definitely and maybe ) when compared to control. There were no differences in diurnal cortisol measures in Study 3. Conclusion: This is the first study to investigate how different aspects of being on-call affect physiological stress responses. Overall, relatively little differences in measures of overnight heart rate variability and next-day cortisol response were recorded in all three studies. Further research utilising real on-call work tasks, not just on-call expectations (as in the current study) will help determine the impact of on-call work on the physiological stress response.